Quarantine and Mental Health Challenges for Occupational Medicine: The Case Report of a Nurse Infected With SARS-CoV-2. (January 2022) - Buselli, R.; Corsi, M.; Veltri, A.; Baldanzi, S.; Chiumiento, M.; Del Lupo, E.; Marino, R.; Necciari, G.; Caldi, F.; Perretta, S.; Foddis, R.; Guglielmi, G.; et al.
This case study draws attention to the psychosocial difficulties that emerged in the context of the coronavirus disease 2019 (COVID-19) outbreak in relation to the remote management of subjects with psychiatric vulnerabilities following exposure to prolonged quarantine. The case involves a 56-year-old hospital nurse, followed by the Occupational Health Department of a major university hospital in central Italy for mood instability in the context of a cyclothymic temperament. She was quarantined for occupationally acquired COVID-19 and remained positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) via swab test for more than 2 months between March and May 2020. In this case study, we discuss the challenges presented by the risk of a prolonged quarantine in a psychologically vulnerable employee, the need for occupational medicine to provide adequate health surveillance of all health care workers during the COVID-19 pandemic, the effectiveness of telepsychiatry, and the difficulties in formulating a proper treatment strategy.